Assessing pharmacists' perspectives of HIV and the care of HIV-infected patients in Alabama - Davis Pate M; Shell AT; King SR (Centro de Investigaciones y Publicaciones Farmaceuticas, 2012)
Objective: The purpose was to assess factors potentially affecting care pharmacists provide to HIV/AIDS patients including comfort level, confidence, education, experience, professional competence, continuity of care and patient-provider relationship between pharmacists and HIV-infected patients.Methods: A 24-item questionnaire assessed the constructs of this study. Surveys were distributed from October 2009 to April 2010 to pharmacists in Alabama with varying levels of experience treating HIV-infected patients. Chi-square tests determined whether relationships existed between responses, consisting of how often respondents reported treating HIV-infected patients, amount of HIV education respondents had, participants' confidence with HIV/AIDS knowledge and comfort level counseling HIV-infected patients about their medications.Results: Thirty-three percent of the pharmacists cared for HIV-infected patients on a monthly basis, yet 86% do not feel very confident with their HIV/AIDS knowledge. Forty-four percent were not comfortable counseling patients on antiretroviral medications, and 77% would feel more comfortable with more education. Significant, positive relationships were revealed concerning how often respondents treat HIV-infected patients and their comfort level counseling them (r=0.208, p<0.05). Similar relationships pertaining to the amount of education respondents had regarding HIV, how confident they are in their HIV/AIDS knowledge (r=0.205, p< 0.05), and their comfort level counseling HIV-infected patients on their medications (r=0.312, p<0.01) were found. The time spent treating HIV-infected patients and the education respondents had pertaining to HIV/AIDS related to increased comfort levels concerning counseling patients on their medications.Conclusion: This research uncovered areas where pharmacists can improve care and treatment for HIV-infected patients. Increasing education on HIV/AIDS and treatment options may lead to increased comfort and confidence in therapeutic management. Through changes in pharmacists' perspectives and abilities to care for their patients, the patient-provider relationship could strengthen, potentially leading to improved medication compliance, enhanced overall health, and a better quality of life for HIV-infected patients.